2017
DOI: 10.1007/s00737-017-0787-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cortisol, thyroid-stimulating hormone, and prolactin in peripartum women with major depression

Abstract: Pregnancy and postpartum are periods of high susceptibility to major depression (MD) and other mood disorders. The peripartum period is also a time of considerable changes in the levels of hormones, including cortisol, thyroid-stimulating hormone (TSH), prolactin, gonadotropins, and gonadal steroids. To investigate the relationship between mood and hormonal changes during and after pregnancy, we reviewed published reports of hormonal measures during this time frame, searched via PubMed and Web of Science. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 71 publications
0
58
0
2
Order By: Relevance
“…have examined HPAA and HPTA in samples of patients with schizophrenia and psychosis. Findings from these studies have been examined in meta-analyses and systematic reviews (29)(30)(31). However, many of these markers have not been examined in the same samples.…”
mentioning
confidence: 99%
“…have examined HPAA and HPTA in samples of patients with schizophrenia and psychosis. Findings from these studies have been examined in meta-analyses and systematic reviews (29)(30)(31). However, many of these markers have not been examined in the same samples.…”
mentioning
confidence: 99%
“…Cortisol, a major end product of the HPA axis, has also received significant attention. To date, no conclusive association has been reported between prenatal cortisol levels at rest and subsequent development of PPD, although cortisol levels at rest are documented to be lower starting 1 month postpartum in mothers with PPD compared to non‐depressed mothers . As for cortisol reactivity, there is some evidence suggesting that mothers who subsequently developed PPD show increased cortisol reactivity during pregnancy.…”
Section: Maternal Hormones In Postpartum Depressionmentioning
confidence: 99%
“…77 Interestingly, some research groups have not been able to replicate these results with larger sample sizes and, instead, found no relationship between higher levels of mid- reported between prenatal cortisol levels at rest and subsequent development of PPD, 76,77 although cortisol levels at rest are documented to be lower starting 1 month postpartum in mothers with PPD compared to non-depressed mothers. 75,[80][81][82] As for cortisol reactivity, there is some evidence suggesting that mothers who subsequently developed PPD show increased cortisol reactivity during pregnancy. One study that used the Trier Social Stress Test reported that pregnant mothers who later developed PPD demonstrated increased cortisol response to psychosocial stress.…”
Section: Hpa Axis Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabei schien zunächst der abrupte Entzug von Östrogenen und Progesteron nach der Geburt und Ablösung der Plazenta für die Entstehung postpartaler Depressionen verantwortlich zu sein. Trotz intensiver Bemühungen konnte jedoch der ätiologische Einfluss hormoneller Faktoren noch nicht in ausreichendem Maße geklärt werden [4].…”
Section: Potenzieller Einfluss Von Hormonenunclassified